Pengaruh Kuat Arus Listrik terhadap Medan Magnet di Sekitar Kawat Lurus Berarus - Adelyna Oktavia Nasution; M. Wira Adhitya; Nazhiful Abid; Sazwani Ardhia Sahira; Laila Ali Putri (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
The results of this study aim to investigate the significant impact of electric currents on the magnetic fields surrounding a straight wire conducting current. This phenomenon is a result of the relationship between electric current and magnetic fields, making it a primary focus of scientific research in the field of physics. The method used in this research is descriptive quantitative, with a thorough analysis of the magnetic effects produced by copper wire applied to iron nails. This study found that the intensity of the magnetic field is very high when the number of copper wire turns reaches 20 turns, resulting in an increase in the attracted nails to 10 nails. This shows that the addition of the number of turns affects the magnetic strength in influencing ferromagnetic objects. This research provides a clear depiction of the relationship between electric current and magnetic fields.